2005
DOI: 10.1016/j.acn.2004.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Detecting depression in Alzheimer?s disease: evaluation of four different scales

Abstract: Depression is a frequent condition in Alzheimer's disease (AD). The prevalence of depressive symptoms depends on the severity of dementia and the instruments used. Our aim was to assess the prevalence of depression dependent on the severity of dementia by four different scales: The 15-point Geriatric Depression Scale (GDS), the Montgomery and Asperg Depression Scale (MADRS), the Cornell Scale for Depression in Dementia (CSDD) and the Nurses Observation Scale for Geriatric Patients (NOSGER). The study populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(136 citation statements)
references
References 17 publications
7
119
2
6
Order By: Relevance
“…In research studies, internal consistency, interrater reliability, and concurrent validity were shown to be acceptable, 31,78,162 and the CSDD was shown to have acceptable psychometric properties in severe dementia. 78 Sensitivity to change was demonstrated in a few trials.…”
Section: Depression In Non-pd Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…In research studies, internal consistency, interrater reliability, and concurrent validity were shown to be acceptable, 31,78,162 and the CSDD was shown to have acceptable psychometric properties in severe dementia. 78 Sensitivity to change was demonstrated in a few trials.…”
Section: Depression In Non-pd Patientsmentioning
confidence: 99%
“…78 Sensitivity to change was demonstrated in a few trials. [163][164][165][166] Informed other ratings on the CSDD in patients with dementia were shown to have higher sensitivity for correctly diagnosing depression than other depression scales, including the BDI, the Ham-D, and the GDS (all modified for caregiver rating).…”
Section: Depression In Non-pd Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Montgomery andÅsperg Depression Scale, the Cornell Scale for Depression in Dementia and the Nurses Observation Scale for Geriatric Patients are other possibilities to assess the depression levels in AD patients [51].…”
Section: Psychological Evaluationmentioning
confidence: 99%
“…As depression is one of the most frequent non-cognitive symptoms in AD (to the extent that a pathogenetic relation between depression and AD has been suggested [51]), psychological evaluation is mainly focused on depression symptoms' measurement.…”
Section: Psychological Evaluationmentioning
confidence: 99%